The relationship between sleep quality and dynamic balance in the elderly - Putu Ade Marwanasari; Sayu Aryantari Putri Thanaya; Ni Komang Ayu Juni Antari; Govinda Vittala (Physical Therapy Journal of Indonesia, 2024)
Background: The aging process in older adults will bring comprehensive changes related to the ability of their physiological functions. This condition causes the elderly's sleep patterns to change with various sleep disorders, resulting in poor sleep quality. The decrease in sleep quality in the elderly can affect their quality of life, including balance disorders. This study aimed to determine the relationship between sleep quality and dynamic balance in the elderly. Methods: This research used a cross-sectional study conducted in Nyuh Kuning Traditional Village, Mas, Ubud, Gianyar, in November 2023. The sampling technique used in this study was total sampling with a sample size of 43 people aged 60 years and over. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, and dynamic balance was calculated using the Time Up and Go Test (TUG Test). Results: The research subjects were dominated by the elderly with poor sleep quality, 30 of whom were elderly (69.8%). Meanwhile, in dynamic balance, most research subjects had variations in dynamic balance and mobility, and the result of the TUG Test (+) was 33 elderly (76.7%). The obtained Sig. (2-tailed) value of the correlation between sleep quality and dynamic balance was 0.000 (<0.05). Sleep quality strongly correlates with dynamic balance, with a correlation coefficient (r) of 0.836, indicating a positive relationship. Conclusion: There was a positive significant relationship between sleep quality and dynamic balance in the elderly.